HCCI Engines: Benefits, Challenges and Future Advancements - Fei Yifan (E3S Web of Conferences)
Homogeneous charge compression ignition (HCCI) engines represent a significant advancement in internal combustion engine technology. This study examines the main advantages of HCCI engines, such as increased fuel flexibility, decreased pollution from nitrogen oxides (NOx) and particulate matter, and enhanced thermal efficiency. However, HCCI technology also faces challenges, such as controlling the combustion process and achieving stable ignition across diverse operating conditions. With rapid advancements in information technology and scientific methods, the automotive engine industry has made significant strides in recent years. In response to stricter environmental regulations and the growing popularity of electric vehicles, HCCI engines have gained increasing attention. Despite existing challenges, continued technological improvements are expected to enhance the feasibility and performance of HCCI engines. This paper reviews current research and technological developments, emphasizing the potential of HCCI engines to revolutionize the automotive industry while addressing critical issues that need resolution. Vital potential chances regarding this exciting field is highlighted.